2008
DOI: 10.1002/pssc.200780118
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2‐D nanostructures via metal deposition through a colloidal mask: comparison between thermal evaporation and RF magnetron sputtering

Abstract: Eine völlig neue Verwendung findet Dimethyltitanocen als Katalysator in der intermolekularen Hydroaminierung von Alkinen. Mit diesem preisgünstigen und problemlos handhabbaren Katalysator können Alkine einfach in Imine, Amine und Ketone überführt werden (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Initially, a monolayer of colloidal particles is selfassembled on a Si (111) substrate (purchased from Crystal GmbH) in a hexagonally close-packed arrangement [17]. Although areas without self-assembled nanospheres were observed throughout the surface, domains of closepacked monolayers of the polystyrene (PS) nanospheres extended over several hundred square micrometers and free of defects were observed by microscopy images.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Initially, a monolayer of colloidal particles is selfassembled on a Si (111) substrate (purchased from Crystal GmbH) in a hexagonally close-packed arrangement [17]. Although areas without self-assembled nanospheres were observed throughout the surface, domains of closepacked monolayers of the polystyrene (PS) nanospheres extended over several hundred square micrometers and free of defects were observed by microscopy images.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For a uniform growth and high quality of the thin films we employed the RF magnetron sputtering method [17,18]. Therefore, deposition was achieved using a Varian installation, with the following main components: two magnetrons, a variomatch, a HV-8 Cryo pump and a TM-300 thickness monitor with 6 MHz gold crystal (ScoTech).…”
Section: Deposition Of Azo Thin Filmsmentioning
confidence: 99%
“…Extensive studies have shown that properties of the AZO thin films are highly dependent on the preparation technology, such as: RF magnetron sputtering [10], thermal oxidation [11,12], chemical vapor deposition [12], pulsed laser deposition [2,13,14], spray pyrolysis [15] and thermal deposition [16]. From these techniques, RF magnetron sputtering [10,17] is considered optimal in terms of high deposition rate, good control and the possibility of scaling to large areas (deposition on large substrates, e.g. 10 cm × 10 cm), high quality of deposition and without emission of toxic gases.…”
Section: Introductionmentioning
confidence: 99%
“…Most notable is the fact that the inner diameter of the rings (270 nm) is smaller than the outer diameter of the reshaped nanospheres (318 nm). This can only result from build up of material under the overhang of the spheres, a phenomenon that can result either from metal atoms undergoing secondary collisions before deposition or, alternatively, metal atoms impacting the surface obliquely [50][51][52]. Both processes are more pronounced in sputtering than in evaporation.…”
Section: Metal Deposition Through the Shaped Nanosphere Mask And Nano...mentioning
confidence: 99%
“…When metals are sputtered the atoms impact the surface at many angles; additionally, the atoms are often moving fast enough to undergo significant secondary scattering off the substrate. For these reasons, sputtering is known to less faithfully reproduce the clean edges of masks because it can build up material under features [50,51]. In this application, the consequences of non-directional deposition are wider nanostructures with much smaller inner diameters (typically 15% less) than the collapsed sphere dimensions.…”
Section: Control Over Nanoring and Nanocrescent Featuresmentioning
confidence: 99%